ANALISIS BIAYA DAN RASIONALITAS PENGOBATAN EKSASERBASI ASMA PASIEN RAWAT INAP - Amelia Lorensia; Marthy Meliana Ariyanti Jalmav; Lafia Lailatul Fadik (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2024)
Asthma is a heterogeneous disease characterized by chronic airway inflammation and asthma-related costs are very high. The aim is to determine cost analysis and evaluate the difference in real costs with INA-CBG’s rates, and evaluate the rationality of treating asthma exacerbations. This design is retrospective by looking at medical record data of patients with asthma exacerbations at RSU Anwar Medika Sidoarjo, for the period January 2020-December 2022. The variables are the real costs and rates of INA-CBGs, and the incidence of drug-related problems (DRPs) of patient treatment data during in the hospital. The data collection method is by observing medical record data and details of medical costs. Data analysis used Mann-Whitney to determine differences in real costs and rates for INA-CBGs. Analysis of rational treatment with MTO is presented descriptively. The number of respondents was 108, with mild (85.19%) and severe (14.81%) asthma rates. The highest direct costs were incurred for accommodation room costs and laboratory costs. The results of the Mann-Whitney test showed that the p value of 0.096 was greater than the alpha value of 0.05, it was concluded that there was no difference in real costs compared to the INA-CBGs rate in asthma patients. Of the patients who experienced MTO, 63 samples (51.21%) experienced DRP and 60 samples (48.78%) did not experience DRP, so it can be concluded that the percentage of DRP events is still high. The total number of DRP incidents that occurred was 182 cases, and the types of DRP that occurred most frequently were unnecessary medication in 179 cases (98.35%) and suboptimal drug effects in 3 cases (1.65%).